2020
DOI: 10.3390/catal10010141
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Non-Precious Transition Metal/Nitrogen-doped Carbon for Oxygen Reduction Electrocatalysts in PEMFCs

Abstract: The proton exchange membrane fuel cells (PEMFCs) have been considered as promising future energy conversion devices, and have attracted immense scientific attention due to their high efficiency and environmental friendliness. Nevertheless, the practical application of PEMFCs has been seriously restricted by high cost, low earth abundance and the poor poisoning tolerance of the precious Pt-based oxygen reduction reaction (ORR) catalysts. Noble-metal-free transition metal/nitrogen-doped carbon (M–NxC) catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 139 publications
(145 reference statements)
0
25
0
Order By: Relevance
“…The specifications for a fuel cell system consist of establishing the performance, dimension, weight and size, emissions, output power, rapid start-up, and rapid response to changes in load, lifetime, and operability in intense environments and noise, which play an important role in certain applications. Great attention has been paid to replacing platinum group metals with carbon-based non-precious metal, nanoporous metals [ 333 , 334 , 335 ], heteroatom-doped carbons [ 336 ], covalent organic frameworks [ 337 , 338 ], non-precious metal, or precious-metal-free catalysts of inexpensive metals [ 339 , 340 , 341 ] as a promising new generation of electrocatalysts has emerged. This is due to their reduced cost, enhanced performance, and high stability and activity of fuel cell applications.…”
Section: Performance Of Single Monocells—pemfcsmentioning
confidence: 99%
“…The specifications for a fuel cell system consist of establishing the performance, dimension, weight and size, emissions, output power, rapid start-up, and rapid response to changes in load, lifetime, and operability in intense environments and noise, which play an important role in certain applications. Great attention has been paid to replacing platinum group metals with carbon-based non-precious metal, nanoporous metals [ 333 , 334 , 335 ], heteroatom-doped carbons [ 336 ], covalent organic frameworks [ 337 , 338 ], non-precious metal, or precious-metal-free catalysts of inexpensive metals [ 339 , 340 , 341 ] as a promising new generation of electrocatalysts has emerged. This is due to their reduced cost, enhanced performance, and high stability and activity of fuel cell applications.…”
Section: Performance Of Single Monocells—pemfcsmentioning
confidence: 99%
“…The NPMCs are based on transition metals dispersed on nitrogen-doped carbon [70,71]. Generally, the structure of NPMCs can be expressed as M − N (2 or 4) − C, where M denotes the transition metal [72]. The typical structure is depicted in Figure 3b, the metal atom is coordinated into four nitrogen atoms (metal chelate).…”
Section: Non-precious Metal Catalystmentioning
confidence: 99%
“…Many investigations have focused on the role of the relationship between electronic charge transfer and catalytic energy barriers [12,[14][15][16][17][18]. Recent work has shown that magnetic moment also plays a role in the catalytic reactivity of O 2 , which is unusually stable with a triplet ground state [19]. Distinguishing the effects of spin state from more traditionally investigated mechanisms such as charge transfer requires understanding the spin polarized density of states of SAC environments, which is most readily accessible with a first principles approach.…”
Section: Introductionmentioning
confidence: 99%